Pengaruh Penambahan Serbuk Daun Kelor (Moringa oleifera) Terhadap Komposisi Proksimat, Kadar Fenol, dan Evaluasi Sensoris Selai Daun Kelor - Fitriarni, Dian; Nova Zulfahmi, A.; Assrorudin, Assrorudin; Ramadani, Dila (Politeknik Negeri Ketapang, 2024)
A healthy lifestyle prioritizes nutritious sources to be processed into products that are common and liked by the public, such as processing Moringa leaves into jam. This is an effort to reduce malnutrition rates. The method for processing Moringa leaf jam refers to the general jam processing process, but is quite difficult because of the different characteristics of Moringa leaves and fruit. This experimental research aims to develop techniques for processing jam made from Moringa leaves, evaluating proximate tests, phenol content and sensory properties. The test samples consisted of jam with different percentages of Moringa leaf powder P0 (control), P1 (1%), P2 (1.5%), and P3 (2%). Data processing uses ANOVA (p>0.05). There was an increase in ash content, protein, fat and fiber content although there was no significant difference. Ash content increased from control 0.847% to 3.65% (P3) as well as protein from 1.323% (control) to 2.078% (P3). Fat increased from 1.121% (P1) to 1.126% (P3), the fiber percentage showed the lowest control value changed to 1.22% (P1) to 1.54% (P3). There is a decrease in water content and carbohydrate content. Water content from 34.19% (P1), 33.86% (P2), to 33.43% (P3) while carbohydrates from 58.86% (P1), 58.98% (P2), and 56.79 % (P3) with the highest value in controls (62.65%). Overall acceptance of Moringa leaf jam products by panelists received a score between 4.2-6.95 in terms of aroma, taste, texture and taste, getting a response of liking to very liking, while the color decreased with increasing percentage of Moringa leaf powder.